Narratives of Pain and Survival: Psychological Trauma in Dalit Autobiographical Writings - Dr. Suraj Jaiswal; Dr. Jay Kumar (The Bioscan, 2026)
The stories of Dalit life articulate both the extreme psychological impact of caste-based discrimination and lend expressions of opposition and resistance to such discrimination. Based on the trauma theory, and especially the work of Cathy Caruth, the study explores the processes behind the caste discrimination as a latent and internalised precipitate of violence that affects the emotional experience, memory, and identity building. Dalit autobiographies prove humiliation, isolation, and shame are not accidental cases, but apparently built into everyday life, with long-lasting psychological consequences.